Which internet content is often used and influenced behavior? A phenomenology about students in senior high school - Martiana, Aris; Dwiningrum, Siti Irene Astuti; Retnawati, Heri; Setiawan, Caly (Universitas Negeri Yogyakarta, 2023)
At present, most students in the world, as well as Indonesia, especially senior high school students, have used the Internet for various purposes. Internet content presented on different platforms can now be accessed easily. Consciously or not, this media content influences their behavior. There is a lot of freely submitted content, which is worth knowing the impact. The question related to this study is which internet content is often used and affects high school students' behavior. Qualitative methods with phenomenology have informants from the western, central, and eastern parts of Indonesia. Data were collected using observation, Google Forms, and interviews for the selected. It uses a sampling technique of 39 informants. The validity of the research used is source triangulation in the next stage, namely analyzing data with Milles & Huberman interactive analysis. Data analysis carried out is data collection, data reduction, data presentation, and conclusion. Content often used is entertainment and educational content, while content that can influence behavior is entertainment, education, health, food and cuisine, religious, beauty, motivational, art, and game content. The content is accessed through various platforms such as social media: YouTube, TikTok, Instagram, Twitter, podcasts, etc.